Park environments and youth physical activity: exploring the influence of proximity and features across Kansas City, Missouri. - Besenyi, Gina M. (Kansas State University, 2011)
Background: With the dramatic increase in childhood obesity rates over the last three decades, parks can offer an accessible and affordable population-level solution to the important issue of youth physical inactivity. The primary purpose of this study was to examine the association of park proximity and park features with nearby youth achieving recommended levels of physical activity. Methods: This community-based study was conducted in Kansas City, Missouri. Valid physical activity data were obtained for 191 youth via a parent proxy survey with an overall response rate of 27.4%. Geographic information systems (GIS) were used to create three measures of park proximity within 1 mile of children’s homes. Detailed park characteristic information for all parks within 1 mile of the youth (n=146 parks) was obtained via observational audits. Binary logistic regression analyses were used to examine the relationship between each park proximity and park characteristic variable and the likelihood of youth meeting physical activity recommendations, while controlling individual and neighborhood level covariates. Results: All youth and female youth who had a park within one-half mile of home were more likely to achieve physical activity recommendations than those with no parks nearby. Likewise, all youth and male youth with three or more parks within 1 mile were significantly more likely to achieve physical activity recommendations than those with only 1 park. Further, youth that had a park with a playground within one-half mile or a baseball field within 1 mile of their home were more likely to achieve physical activity recommendations. Finally, having a park with particular amenities within 1 mile from home (transit stops, traffic signals, picnic tables, grills, trash cans, shade, and roads through the park) was also associated with greater odds of achieving physical activity recommendations. Conclusions: Parks are valuable community resources that can play an important role in the battle against rising rates of obesity and chronic disease in youth across the country. Better understanding the ways in which these settings are associated with physical activity among children can inform future research and environmental and policy changes that can promote the health and well-being of generations to come.
Keywords: Physical activity; Youth; Park; Environment; Proximity; Features; Kinesiology (0575); Public Health (0573); Recreation and Tourism (0814)